Passage of Abrikosov Vortexes through a Boundary Barrier in Thin Superconducting Film - Pyragas, V. (Nonlinear Analysis: Modelling and Control, 2004)
The model of Abrikosov vortices motion from the edges of thin superconducting film, when the current slightly exceeds the critical current, is considered. It is shown that the additional dynamic barrier is formed in the regions of a weak pinning. It is assumed for simplicity that the group of vortices is derived in the shape of one-dimensional chain. It is demonstrated, that the barrier hinders the penetration of such a chains in the film.
Keywords: superconductivity; vortex motion; thin film; pinning centers